Ethnoscience-Based Physics Learning on the Topic of Sound Waves to Enhance Students’ Creativity: A Mixed-Methods Approach - Zulkarnaen Zulkarnaen; Nevi Ernita (International Journal of Ethnoscience and Technology in Education, 2026)
This study addresses the need to foster students’ creativity in physics learning, particularly on abstract topics such as sound waves, through instruction that is more meaningful, contextual, and culturally relevant. Conventional physics teaching at the junior secondary level often remains teacher-centered and procedural, limiting opportunities for students to explore ideas and develop creative thinking. Therefore, this study aimed to examine whether ethnoscience-based physics learning on the topic of sound waves could improve students’ creativity, to determine the extent of improvement, and to describe how creativity emerged during the learning process. The study employed an embedded mixed-methods design. Quantitatively, it used a one-group pretest-posttest design involving 20 Grade VIII students from one junior high school in Mataram City, Indonesia. Qualitatively, classroom observations, field notes, and learning documentation were used to capture students’ engagement and manifestations of creativity. Quantitative data were analyzed using descriptive statistics, N-gain, and one-way repeated measures ANOVA, while qualitative data were analyzed through descriptive thematic analysis. The results showed a substantial improvement in students’ creativity. The mean score increased from 43.75 in the pretest to 81.38 in the posttest, with a mean N-gain of 0.80. The repeated measures ANOVA indicated a significant effect, F(1, 19) = 491.97, p < .001, with a very large effect size (partial eta squared, η² = 0.963). Qualitative findings revealed increased participation, richer idea generation, and stronger connections between physics concepts and local cultural contexts. It is recommended that ethnoscience-based learning be applied more widely in physics instruction and examined further across broader contexts and topics.